2017
DOI: 10.1002/adfm.201703982
|View full text |Cite
|
Sign up to set email alerts
|

Nanoformulation of Brain‐Derived Neurotrophic Factor with Target Receptor‐Triggered‐Release in the Central Nervous System

Abstract: Brain-derived neurotrophic factor (BDNF) is identified as a potent neuroprotective and neuroregenerative agent for many neurological diseases. Regrettably, its delivery to the brain is hampered by poor serum stability and rapid brain clearance. Here, a novel nanoformulation is reported composed of a bio-compatible polymer, poly(ethylene glycol)--poly(L-glutamic acid) (PEG-PLE), that hosts the BDNF molecule in a nanoscale complex, termed here Nano-BDNF. Upon simple mixture, Nano-BDNF spontaneously forms uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 50 publications
8
78
0
3
Order By: Relevance
“…The flow cytometric results indicated that the internalization of SiPINGs was significantly inhibited by genistein, CPZ, amiloride, sodium azide, and 4 °C treatment (Figure S9, Supporting Information), revealing the caveolin‐, clathrin‐, and macropinocytosis‐mediated endocytosis. Meanwhile, SiPINGs presented favorable biocompatibility with low dark‐ and photo‐toxicities detected by 3‐(4,5‐dimethyl‐2‐thiazolyl)‐2,5‐diphenyl‐2‐ H ‐tetrazolium bromide (MTT) and flow cytometry‐based apoptosis assays (Figure c,d; Figure S8c,d and Table S1, Supporting Information), which can be credited to the biocompatible components (including PEG–PLE, silicon‐containing nanomaterials, and United States Food and Drug Administration (FDA)‐approved ICG) and the very low content of ICG (which could not cause a significant temperature increase in the cells). The results also suggested that the high intracellular local concentration of ICG had negligible influence on the cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…The flow cytometric results indicated that the internalization of SiPINGs was significantly inhibited by genistein, CPZ, amiloride, sodium azide, and 4 °C treatment (Figure S9, Supporting Information), revealing the caveolin‐, clathrin‐, and macropinocytosis‐mediated endocytosis. Meanwhile, SiPINGs presented favorable biocompatibility with low dark‐ and photo‐toxicities detected by 3‐(4,5‐dimethyl‐2‐thiazolyl)‐2,5‐diphenyl‐2‐ H ‐tetrazolium bromide (MTT) and flow cytometry‐based apoptosis assays (Figure c,d; Figure S8c,d and Table S1, Supporting Information), which can be credited to the biocompatible components (including PEG–PLE, silicon‐containing nanomaterials, and United States Food and Drug Administration (FDA)‐approved ICG) and the very low content of ICG (which could not cause a significant temperature increase in the cells). The results also suggested that the high intracellular local concentration of ICG had negligible influence on the cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…Evacuated tubes were used to collect venous blood samples and ethylenediaminetetraacetic acid dipotassium was used as an anticoagulant. All plasma samples were processed as previously described (22)(23)(24). The plasma samples were processed in a centrifuge at 3,000 x g for 10 min at 4˚C and separated into a RNase-free tube.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, uniform core-shell self-assembled particles, based on poly(ethylene glycol)-b-poly(l-glutamic acid) (PEG-PLE), were proposed to stabilize and to improve BDNF delivery throughout the brain (Jiang et al, 2018).…”
Section: Alternative Nanocarriers For Protein Deliverymentioning
confidence: 99%